Program pelatihan peningkatan kapasitas perangkat desa Wonggahu kabupaten Boalemo - Mohamad Jahja; Meilan Demulawa (Univeristas Negeri Gorontalo, 2022)
The capacity training program for the village apparatus of Wonggahu, Boalemo district, was carried out by KKN students from September to October, covering village digitization workshops, covd-19 vaccination program and BIMTEK.